Sex-Gender Differences in the Effectiveness of Treatment of Irritable Bowel Syndrome: A Systematic Review - van Kessel, Lente (Int J Gen Med, 2021)
BACKGROUND: In recent years, research on sex-gender differences in health care has increasingly recognized that men and women differ in the way symptoms occur, in risk factors for certain conditions and in the way they respond to the same treatment. A disease that is known to often present differently in women and men is irritable bowel syndrome (IBS). Given the difference in prevalence, predominant symptoms and possible other pathophysiology, it is conceivable that a difference in treatment effectiveness in men and women is a discovery waiting to be found. PURPOSE: To determine whether there are differences in treatment effectiveness between men and women with irritable bowel syndrome. MATERIALS AND METHODS: We searched on PubMed and EMBASE, selecting randomized controlled trials comparing IBS treatment in men and women over 18 years old. One researcher performed the inclusion process, and two researchers independently performed a quality assessment. A descriptive analysis was conducted. RESULTS: Twelve studies, randomizing 1847 men and 3562 women, were included in this review. Treatment with serotonin antagonist alosetron, treatment with ibodutant and crofelemer and adding cognitive behavioral therapy to medical treatment found significant differences between men and women in favor of effectiveness towards women in either satisfactory relief of overall IBS symptoms or percentage of pain-free days. CONCLUSION: Sex-gender can be a determining factor in the effectiveness of IBS treatment. Due to the limited number of studies per treatment option, no recommendations can be made on the choice of a specific treatment. It is clear, however, that so as not to miss beneficial treatment options for either sex, the inclusion, analysis and description of data on the basis of sex is of the utmost importance.